8x+8
24-3a
6y+30
2007-01-19 07:23:29
·
answer #1
·
answered by luc564 2
·
0⤊
0⤋
9x+5-x+3 = 9x - x + 5 +3
= 8x + 8
[ = 8(x+1) ]
-3(a-8) = -3a + 24 (remember -3 x -8 gives +24)
(This was already in its simplest form, and in this case was expanded)
10(y+3) - 4y = 10y +30 - 4y
= 10y - 4y + 30
= 6y + 30
[ = 6(y+5) ]
If you need help in understanding 'how' the answers were obtained, email me and I'll explain it further.
Don't just write the answers down without understanding, or you'll get caught out later.
(Note: I'm 40 years old and had to come back and edit this because I made a basic error... oops)
Chris
2007-01-19 15:27:33
·
answer #2
·
answered by Shiner 2
·
0⤊
0⤋
8x + 8= x +1
-3a+24 = a -8
10y +30 - 4y = 6 y +30= y +5
2007-01-19 15:25:49
·
answer #3
·
answered by eb 1
·
0⤊
0⤋
8x + 5+3
8x+8 for the first one.
and
-3a -(-24) which changes into a positive, so 3a+24
and 10y +30 -4y so, you simplify, to 6y plus thirty. Good luck!
2007-01-19 15:24:51
·
answer #4
·
answered by me 1
·
0⤊
0⤋
9x+5-x+3 = 8x+8
-3(a-8) = 24-3a
10(y+3)-4y = 10y+30-4y = 6y+30
Good Luck!
2007-01-19 15:25:48
·
answer #5
·
answered by Slay Specialist 3
·
0⤊
0⤋
OK combine the common factors: 8x +8-3a +24 + 10y + 30 -4y
equals
8x + 62 -3a + 6y
2007-01-19 15:25:12
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
8x+8
-3a+24
10y+30-4y = 6y+30
2007-01-19 15:28:18
·
answer #7
·
answered by Krista C 2
·
0⤊
0⤋
9x + 5 - x + 3
(group like terms)
9x - x + 5 + 3
(simplify)
8x + 8
(remove common factors)
8(x + 1)
(multiply through)
-3a+ 24
(if you need this, "-3(a-8)" is 'simple'
10(y+3)-4y
(multiply through)
(group like terms)
(remove common factors)
2007-01-19 15:28:01
·
answer #8
·
answered by RichardPaulHall 4
·
1⤊
0⤋
Add like terms. The first answer is 8x+8, the second answer is -3a+24, and the third answer is 6y+30.
2007-01-19 15:24:45
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
8x + 8
-3a + 24
6y + 30
2007-01-19 15:24:07
·
answer #10
·
answered by ? 5
·
0⤊
0⤋
8x+8
-3a+24
6y+30
2007-01-19 15:24:32
·
answer #11
·
answered by Christine 4
·
0⤊
0⤋